Why vehicle architecture is so important for comfort dynamics? Certain analysis tools of comfort dynamics for vehicle architectures. (16th June 2021) - Dion, Jean-Luc; Cumunel, Gwendal; Rameau, Jean-François
Highlights: Nonlinear filtering analysis. Vibration comfort metric for embedded systems in articulated mechanism. Kinematic solver based on generalised cross product. Abstract: Ground vehicle architectures are designed to prevent the transmission of vibration, shock, and noise from the ground profile under operating conditions. The choice of a kinematic architecture strongly contributes to the filtering efficiency of the complete system and has to be considered before the efficiency of the suspension components. In order to highlight the filtering contribution of architectures, all flexible (and dissipative) behaviours are removed in studied models: all the components are assumed as rigid bodies. Thus, this paper focuses on the kinematic filtering performed by ground vehicle architectures, especially articulated suspension systems. The proposed methodology for studying the filtering efficiency of ground vehicle architectures is described and illustrated by the study of a single wheel to that of the rocker-bogie system used for the rover Curiosity, passing through the intermediate case of a bicycle. Firstly, an original and robust method is proposed in order to simulate this type of mechanism. For this purpose, the kinematics of the studied system is defined by algebraic equations transformed into a set of ordinary differential equations by using an adaptation of the generalized cross product. Secondly, the nonlinear filtering effect of the kinematic function of the system is studied and discussed. This paper provides a set of nonlinear analysis tools applied to kinematics of a ground vehicle, to characterize and analyse architectural designs. The two main contributions of this work are, first, a kinematic solver method based on generalised cross product, and secondly, dedicated vibration comfort metrics for embedded systems in articulated mechanism (based on nonlinear filtering analysis).